2006
DOI: 10.1055/s-2006-924277
|View full text |Cite
|
Sign up to set email alerts
|

Correlated Expression of gfp and Bt cry1Ac Gene Facilitates Quantification of Transgenic Hybridization between Brassicas

Abstract: Gene flow from transgenic oilseed rape (BRASSICA NAPUS) might not be avoidable, thus, it is important to detect and quantify hybridization events with its relatives in real time. Data are presented showing the correlation between genetically linked green fluorescent protein (GFP) with BACILLUS THURINGIENSIS (Bt) CRY1AC gene expression in hybrids formed between transgenic B. NAPUS "Westar" and a wild Chinese accession of wild mustard (B. JUNCEA) and hybridization between transgenic B. NAPUS and a conspecific Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The third generation of the progenies of transgenic event 1 was used in this study. F 1 hybrids were produced by pollinating ten wild brown mustard plants of that local seed collection with pollen from more than ten transgenic OSR (GT) plants in a greenhouse 36…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The third generation of the progenies of transgenic event 1 was used in this study. F 1 hybrids were produced by pollinating ten wild brown mustard plants of that local seed collection with pollen from more than ten transgenic OSR (GT) plants in a greenhouse 36…”
Section: Methodsmentioning
confidence: 99%
“…Seedling emergence was recorded after removal of the agricultural film in the spring. At the beginning of April 2006, plants were culled to one plant per location following GFP fluorescence screening and transgene PCR analysis of F 1 hybrids 36. The result of this assay was the retention of transgenic F 1 hybrids and removal of non‐transgenic plants.…”
Section: Methodsmentioning
confidence: 99%
“…Correlated expression of Bt cry1Ac and GFP transgenes is caused by the regulation of identical but independent CaMV 35S promoters with cassettes located linked on the same genomic locus (Harper et al , 1999; Halfhill et al , 2001). An early finding was reported for the correlated expression of the two genes at the vegetative growth stage (Shen et al , 2006). Here we reported again the correlation at reproductive stages.…”
Section: Discussionmentioning
confidence: 95%
“…The GFP gene cloned from the jellyfish ( Aequorea victoria ) is a useful in vivo real‐time marker for monitoring transgenes when coupled to another transgene (Stewart, 1996, 2005). The correlated expression of Bt and GFP genes in hybrid could facilitate the detection of hybridization in the field (Shen et al , 2006) and also relative gene expression of a second gene (Harper et al , 1999). In one study, Shen et al (2006) demonstrated a close correlation between Bt Cry1Ac protein and GFP fluorescence in hybrids formed between transgenic B. napus and wild B. juncea at vegetative growth stage but no such test has been yet conducted at the reproductive growth stage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation